Private Sector Performance Measures and Thier Applicability to Government Operations. - Rubin, Marc A.; Moriarity, Shane R. (The Accounting Review, 1992)
Abstract Reviews the book `Private Sector Performance Measures and Their Applicability to Government Operations,' by David J. Harr and James T. Godfrey.